Nasal Residence Depending on the Administered Dosage Form: Impact of Formulation Type on the In Vivo Nasal Retention Time of Drugs in Rats - Daisuke Inoue; Yoshihiro Seto; Hideto To (Pharmaceutics)
Background/Objectives: The precise control of drug absorption through the nasal mucosa following intranasal administration can be achieved through optimal formulation development that considers the nasal retention properties of the administered dosage form. This study aimed to quantitatively elucidate the effect of formulation type on nasal residence time in vivo. Methods: The nasal residence behavior of various formulation types, including solutions, particulates, and powders, was estimated in rats. Furthermore, the effect of mucoadhesive polymers on the nasal residence time was investigated using gel and powder dosage forms of sodium alginate. Results: The nasal retention behavior of the formulation in the nasal cavity differed depending on the dosage form. The polystyrene microparticles and lactose powder, a non-adhesive powder, were quickly eliminated into the nasopharynx, whereas the solution remained in the nasal cavity longer than the other formulations. The clearance behavior of the solution was investigated, and it was found that the solution was quickly transported to the stomach without being retained in the esophagus. The disappearance of the gel and powder with the mucoadhesive polymer was different, with the powder clearing faster. This difference in clearance is thought to be due to the powder being cleared before dissolving and diffusing into the nasal mucus. Conclusions: It has been clearly shown that the nasal residence behavior differed depending on the dosage forms. The addition of mucoadhesive polymers was effective in improving the nasal residence of the drug, and more-effective formulations for nasal application can be developed by combining optimal dosage forms, such as powders and gels.